Radiation Therapy to Sites of Metastatic Disease as Part of Consolidation in High-Risk Neuroblastoma: Can Long-term Control Be Achieved? - Casey, Dana L; Pitter, Ken L; Kushner, Brian H; Cheung, Nai-Kong V; Modak, Shakeel; LaQuaglia, Michael P; Wolden, Suzanne L (International journal of radiation oncology, biology, physics, 2018)
As part of consolidative therapy in high-risk neuroblastoma, modern protocols recommend radiation therapy (RT) both to the primary site and to sites of metastatic disease that persist after induction chemotherapy. Although there are abundant data showing excellent local control (LC) with 21 Gy directed at the primary site, there are few data describing the feasibility and efficacy of RT directed at metastatic sites of disease as part of consolidation. All patients with neuroblastoma who received RT to metastatic sites of disease as a part of consolidative therapy at a single institution between 2000 and 2015 were reviewed. Among 159 patients, 244 metastases were irradiated. The median follow-up period among surviving patients was 7.4 years. Over 85% of the irradiated metastases were treated with 21 Gy (range, 10.5-36 Gy). Tumor recurrence occurred in 43 of 244 irradiated metastases (18%). The 5-year LC rate of treated metastatic sites was 81%. Metastatic sites that cleared with induction chemotherapy had improved LC compared with sites with persistent uptake on metaiodobenzylguanidine scans (LC rate, 92% vs 67%; P < .0001). LC at irradiated metastatic sites did not differ based on total number of sites irradiated or site of disease irradiated (bone vs soft tissue). Patients with bulky, resistant disease who were treated with 30 to 36 Gy had worse LC (P = .02). However, on multivariate analysis, only persistence after induction chemotherapy remained a significant prognostic factor for LC (hazard ratio, 3.7; P < .0001). Patients who had LC at irradiated metastatic sites had improved overall survival compared with those who did not (overall survival rate, 71% vs 50%; P < .0001). Response to chemotherapy is an important prognostic factor for LC at irradiated metastatic sites in neuroblastoma. Overall, consolidative RT appears to be an effective modality of LC. Long-term disease control can be achieved with such an approach.